Unveiling Student Experiences with Project Based Learning (PjBL): Insights from Jambi University - Tersta, Friscilla Wulan; Berliana, Winny; Safitri, Nyimas Triyana; Anastasia, Indri (SCOPE: Journal of English Language Teaching, 2024)
The purpose of this research is to find out the perceptions of students towards Project Based Learning (PjBL)-based learning at one of study program in Jambi University which has been implemented for approximately 2 years. This research used a type of qualitative research with a case study. Data collection techniques used by researchers consist of observation, interview and documentation techniques. There are six themes emerged in this research: Learning experiences, Long-term Memory Retention, Student Creativity Enhancement, Time Intensiveness, Leadership Development and Responsibility, Flexibility in Learning. It is suggested that further research and exploration be conducted to address the challenges and preferences identified by students and lecturers regarding PjBL.